The factors that determine successful follow up of children diagnosed with incurable blindness using health information collected during their visits to the Red Cross Childrens Hospital - Mjwana, Noluthando (Division of General Surgery, 2025)
Background: Most children diagnosed with incurable blindness will need access to health, education, and social services, to support them during their potentially high number of disabled life years. The accuracy of key informants' contact information is therefore essential to ensure that proper follow up is carried out, so that the necessary services are available to them. We investigated the factors determining successful follow up of children diagnosed with incurable blindness during their visits to the Red Cross War Memorial Children's Hospital (RXH) in Cape Town, using their health information. Methods: This was a quantitative cross-sectional study, using data from a cohort of blind children who were referred to a blind school from 2011 to 2020, a total of 178 children, from 0 years up to 12 years of age. Contact information was collected from the children's hospital files at the Red Cross Children's Hospital. Using the telephone numbers obtained, calls were made, and the results of the calls were recorded. For those calls that were responded to, an introduction of who the researcher is, was made, then the purpose and explanation for the call was provided and the respondent was informed that participation is voluntary and that the interview can be stopped at any time should the respondent wish to do so. After that, consent to proceed with an interview was requested, and after it was granted, the researcher explained to the respondent that a few questions about the child's whereabouts, and basic information about health, education and social activities will be asked. A second round of calls were made, using an identifiable cell phone number. This was to ensure that for all the parents or guardians with whom contact was made but were not reachable for any reason during the initial round, a second attempt was made to reach them. Lastly, the nurse of the blind school was interviewed to triangulate the results of the telephonic interviews. The interview with the nurse was to confirm, whether the children on the data list were registered with the school as well as to ascertain the support services that 2 are on offer at the school for the blind. Results: The findings of the study indicated that of the total of 178 participants' folders checked, 127 (71%) folders did contain real and contactable telephone numbers, 10 (6%) folders had incorrectly recorded contact numbers, and 41 (23%) folders had no contact numbers as they were missing. Of the 127 folders with contactable numbers, only 29 (23%) of the key informants responded. Of these, 25 out of 29 (86%) confirmed that the children were alive with 4 (16%) mortalities reported. With regards to information on various support services offered, 7 out of 25 (24%) confirmed to have access to health services, which included hospital visits on scheduled appointment dates, with 16 (64%) receiving support for social services such as grants for relief on financial burden and 15 (60%) of the children are in receipt of education support services or attending special schools. Conclusion: As evidenced by the low response rate, contact with most of the parents was not achieved, resulting in less data to inform us of successful follow of the children. This lack of success can be attributed to the high inaccuracy in the capturing of the contact details, in the missing contact numbers as well as calls for some contacts which were no longer in-service. While little can be done with numbers being out of service, the incorrectly captured information coupled with lack of contact numbers requires that further scrutiny is applied to the patient folders when recording their information and that regular checks and updates are done to ensure that contact numbers are available and that they are accurate.